Yaroslava Pulinovich’s Plays: The Theme of Family and Female Linguocultural Types - Kupina, Natalia A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2019)
The author analyses Yaroslava Pulinovich’s plays (2017), which authentically reproduce the linguistic existence of the modern Russian city. It is noted that Pulinovich’s individual style evolves from the linguistic naturalism inherent in the aesthetic convention of the Ural school of dramatic art to linguistic realism. Analysis of her texts demonstrates that the lexical paradigm, including the nominations house, apartment, and room, supports the theme of family. The subject of the research are stage directions as a text within a text, cues, monologues, and cooperative and conflict dialogues. A linguo-stylistic and axiological interpretation of speech roles of characters allows the author to reach the goal of the research, i.e. reveal the features of conversational family life reproduced in texts. A special task is to characterise the female linguistic culture types, whose formation and development are determined by role rights and duties within a two-parent or a one-parent family. The author singles out means for creating openness and trusting interpersonal communication; she also systematises speech genres, whose automatic reproduction leads to the routine of everyday communication. The author offers a functional explanation of family taboos, verbalised prohibitions, instructions, complaints and recriminations, assurances of superiority, and disparaging evaluations. Egocentrism causing moral degradation is a typical characteristic of a teenage girl concentrated on the idea of personal superiority. The ability for extraordinary actions and need for personal freedom mark the construction of the type of an educated young woman who has been building her life according to the model developed by her mother for a long time. Speech representation of the modality of obligation marks the linguocultural mother type having to bring up her daughter on her own. Pulinovich’s axiological diagnostics of breaking gender stereotypes acquires not only aesthetic, but also social and cultural significance.